Effectiveness and safety of pembrolizumab for patients with advanced non-small cell lung cancer in real-world studies and randomized controlled trials: A systematic review and meta-analysis - Yang, Beibei; Wang, Bing; Chen, Yongbang; Wan, Ning; Xie, Fei; Yang, Ning; Lu, Liqing; Xiao, Weibin; Yuan, Jin; Li, Jian; Xie, Bo; Ji, Bo (Frontiers in Oncology, 2023)
Background Several randomized controlled trials (RCTs) have confirmed the favorable clinical benefit of pembrolizumab in advanced non-small cell lung cancer (NSCLC). However, considering the strict inclusion and exclusion criteria in clinical research, there are certain differences between patients in the real-world, it is unclear whether the findings of clinical trials are fully representative of the treatment efficacy in patients who will eventually use it. Therefore, to further comprehensively assess the efficacy and safety of pembrolizumab in NSCLC, we conducted a systematic review and meta-analysis based on the latest RCTs and real-world studies (RWSs). Methods We systematically searched PubMed, Embase, The Cochrane Library, The Web of Science, and clinical trials.gov as of December 2021. RCTs and RWSs of patients receiving pembrolizumab monotherapy or in combination with chemotherapy for advanced NSCLC were included. Results The meta-analysis ultimately included 11 RCTs and 26 RWSs with a total of 10,695 patients. The primary outcomes of this study were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), serious adverse events (SAEs), the incidence of severe pneumonia reactions, and drug-related mortality. Direct meta-analysis results showed that in RCTs, pembrolizumab in combination with chemotherapy was superior to chemotherapy in terms of OS (HR=0.60, 95%CI:0.50-0.73), PFS (HR=0.47, 95%CI:0.38-0.58) and ORR (OR=3.22, 95%CI:2.57-4.03); pembrolizumab monotherapy was superior to chemotherapy in terms of OS (HR=0.73, 95%CI:0.66-0.80) and ORR (OR=1.90, 95%CI:1.17-3.09), but comparable to chemotherapy in terms of PFS (HR=0.83, 95%CI:0.66-1.04). The ORR values in retrospective single-arm studies were 45% (40%-51%). Conclusion In RCTs, pembrolizumab monotherapy or in combination with chemotherapy is more effective and safer than chemotherapy for advanced NSCLC. In RWSs, ECOG PS 0-1 was shown to correlate with PFS and OS for patients with NSCLC.